Mixed‐methods content and sentiment analysis of adolescents' voice diaries describing daily experiences with asthma and self‐management decision‐making. Issue 3 (18th September 2018) - Mammen, Jennifer R.; Java, James J.; Rhee, Hyekyun; Butz, Arlene M.; Halterman, Jill S.; Arcoleo, Kimberly
Abstract: Background: Accurate symptom assessment remains challenging in teen populations. Little is known of usual symptom/response patterns, and self‐reported paper diaries have traditionally low compliance rates. Therefore, we used concurrent digital voice diaries to capture daily asthma experiences. Objective: (a) To qualitatively explore usual symptom patterns and self‐management responses and (b) to quantitatively explore relationships between symptom severity and sentiment scores (a marker of emotional response to events). Methods: Fourteen minority and nonminority teenagers (age 13‐17) with controlled (50%) and uncontrolled asthma used digital recorders to report about their asthma once daily over 14 days. Dairy entries were coded for symptom frequency, severity, type, and self‐management responses, while sentiment analysis was used to evaluate the emotional valence of diary entries and to explore whether increased symptom levels correlated with greater negative sentiment. Results: Symptom frequency and severity recorded in voice diaries were much higher than teens indicated at baseline and were discordant with clinical assessments of asthma control. Of 175 entries, teens had symptoms 69.1% of days (121/175) and severe symptoms on one‐third of these. Atypical symptoms (coughing, throat clearing) were reported twice as often as traditional symptoms (wheezing, chest tightness) and often not recognized as asthma, but rather attributed to being "sick" (25.6% of symptom days). Teens frequently minimized symptoms, used rescue and controller medication inconsistently, and resorted to alternative strategies to manage symptoms. Sentiment was not significantly correlated with assessed control (β = 0.14, P = 0.28), but for teens reporting severe symptoms, sentiment scores decreased by 0.31 relative to teens without symptoms ( P = 0.006). Conclusions and Clinical Relevance: Teens may minimize symptoms and have greater symptom frequency and severity than is recognized by themselves or providers. Screening for specific symptoms including coughing, throat clearing, and respiratory illness may be needed to identify those experiencing burden from asthma.